Extensor Carpi Ulnaris Instability Following Ulnar Shortening Osteotomy - Noureldin, Mohamed; Kakar, Sanjeev (Journal of Wrist Surgery, 2017)
Background Ulnar shortening osteotomy (USO) is a well-established procedure for the treatment of ulnar impaction syndrome. Although uncommon, the procedure can be associated with complications including nonunion, malunion, and hardware irritation.Case Description We present a 56-year-old woman who developed extensor carpi ulnaris (ECU) tendon instability following an USO.Literature Review The etiology of such a complication can be multifactorial.Clinical Relevance The recurrence of ulnar pain following an USO should raise the suspicion of possible ECU instability within the differential diagnosis.
Keywords: extensor carpi ulnaris instability; ulnar shortening osteotomy